Optimal Extent of Transhiatal Gastrectomy and Lymphadenectomy for the Stomach-Predominant Adenocarcinoma of Esophagogastric Junction: Retrospective Single-Institution Study in China - Zhao, Baoyu; Zhang, Zhenzhan; Mo, Debin; Lu, Yiming; Hu, Yanfeng; Yu, Jiang; Liu, Hao; Li, Guoxin (Frontiers in Oncology, 2019)
Background. The optimal extent of gastrectomy and lymphadenectomy for esophagogastric junction (EGJ) cancer is controversial. Our study aimed to compare the long-term survival of transhiatal proximal gastrectomy with extended periproximal lymphadenectomy (THPG with EPL) and transhiatal total gastrectomy with complete perigastric lymphadenectomy (THTG with CPL) for patients with the stomach-predominant form of EGJ cancer. Methods. Between January 2004, and August 2015, 306 patients with Siewert II tumors were divided into the THTG group (n=148) and the THPG group (n=158). Their long-term survival was compared according to Nishi’s classification. The Kaplan–Meier method and Cox proportional hazards models were used for survival analysis. Results. There were no significant differences between the two groups in the distribution of age, gender, tumor size or Nishi’s type (P>0.05). However, a significant difference was observed in terms of pathological tumor stage (P<0.05). The 5-year overall survival rates were 62.0% in the THPG group and 59.5% in the THTG group. The hazard ratio for death was 0.455 (95% CI, 0.337 to 0.613; log-rank P<0.001). Type GE/E=G showed a worse prognosis compared with Type G (P<0.05). Subgroup analysis stratified by Nishi’s classification, Stage IA-IIB and IIIA, and tumor size ≤ 30 mm indicated significant survival advantages for the THPG group (P<0.05). However, this analysis failed to show a survival benefit in Stage IIIB (P=0.211). Conclusions. Nishi's classification is an effective method to clarify the subdivision of Siewert II tumors with a diameter ≤ 40 mm above or below the EGJ. THPG with EPL is an optimal procedure for patients with stomach-predominant EGJ tumors less than 30 mm in diameter and in Stage IA-IIIA. For more advanced and larger EGJ tumors, further studies are required to confirm the necessity of THTG with CPL.